2002
DOI: 10.1212/wnl.58.5.765
|View full text |Cite
|
Sign up to set email alerts
|

ALS and PDC of Guam

Abstract: Relatives of patients with ALS or PDC have significantly higher risks for developing the disease than the Guamanian population, whereas relatives of controls have significantly lower risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 13 publications
0
42
0
1
Order By: Relevance
“…ALS-PDC is an incurable disease of still unknown etiology. In Guam, PDC and ALS often occur in the same individual and the same families (37).…”
Section: Discussionmentioning
confidence: 99%
“…ALS-PDC is an incurable disease of still unknown etiology. In Guam, PDC and ALS often occur in the same individual and the same families (37).…”
Section: Discussionmentioning
confidence: 99%
“…13), two chanzymes, have long been thought to cause Guamanian amyotrophic lateral sclerosis (ALS-G) and parkinsonism-dementia complex of Guam (PD-G), or parkinsonism-dementia complex, two related neurodegenerative disorders that are endemic in the Western Pacific, including Guam (Plato et al, 2002 , as well as the presence of the putative neurotoxin, L-b-Nmethylamino-L-alanine, derived from the cycad plant (traditionally, bats that feast on cycad plants are considered a delicacy by the natives).…”
Section: Melastatin Transient Receptor Potential Channelopathiesmentioning
confidence: 99%
“…After 25 years, in 1983, it was clear that there was a significantly higher risk for ALS and PDC among parents, siblings and spouses of patients than among relatives of controls without symptoms (Plato et al, 2002). Also in the follow up after 40 years, relatives, siblings and wives to ALS patients, but not husbands to ALS patients, had a higher risk for ALS or PD than Chamorro people in general.…”
Section: Ruling Out Inheritance As the Major Cause Of Als-pdcmentioning
confidence: 99%
“…Some categories of relatives to PD patients had a higher risk for both ALS and PD than the population in general, and higher risk for PD than Chamorro in general. The most important finding was that children to patients with PD had an increased risk for ALS and PD, but children to patients with ALS did not have an increased risk to acquire the diseases (Plato et al, 2002;Waring et al, 2004). Poorkaj et al (2001) concluded that the disease clusters in families, indicates the importance of inheritance for ALS-PDC susceptibility, whereas the change in men to women ratio (2.5 to 1.5) and incidence over time and corresponding change in onset age suggests that gene-environment interactions are important.…”
Section: Ruling Out Inheritance As the Major Cause Of Als-pdcmentioning
confidence: 99%
See 1 more Smart Citation